Polymorphisms and genomic organization of repetitive DNA from centromeric regions of Arabidopsis chromosomes. - Heslop-Harrison, J S (1999)
A highly abundant repetitive DNA sequence family of Arabidopsis, AtCon, is composed of 178-bp tandemly repeated units and is located at the centromeres of all five chromosome pairs. Analysis of multiple copies of AtCon showed 95% conservation of nucleotides, with some alternative bases, and revealed two boxes, 30 and 24 bp long, that are 99% conserved. Sequences at the 3' end of these boxes showed similarity to yeast CDEI and human CENP-B DNA-protein binding motifs. When oligonucleotides from less conserved regions of AtCon were hybridized in situ and visualized by using primer extension, they were detected on specific chromosomes. When used for polymerase chain reaction with genomic DNA, single primers or primer pairs oriented in the same direction showed negligible amplification, indicating a head-to-tail repeat unit organization. Most primer pairs facing in opposite directions gave several strong bands corresponding to their positions within AtCon. However, consistent with the primer extension results, some primer pairs showed no amplification, indicating that there are chromosome-specific variants of AtCon. The results are significant because they elucidate the organization, mode of amplification, dispersion, and evolution of one of the major repeated sequence families of Arabidopsis. The evidence presented here suggests that AtCon, like human alpha satellites, plays a role in Arabidopsis centromere organization and function.